Penerapan Pembelajaran Problem Based Learning Berbasis Blended Learning terhadap Hasil Belajar Kognitif dan Motivasi Mahasiswa - Setyoko Setyoko; Indriaty Indriaty (Jurnal Pendidikan Biologi, 2018)
Learning innovation in Higher Education with a scientific approach based learning has been integrated with Information and Communication Technology. This encourages students to solve problems in accordance with the real conditions in the surrounding environment. In addition, it can create self-reliance and learning motivation for students to learn science without any time and place limitation. This study aims to implement scientific approach based learning through the Problem Based Learning model based on Blended Learning in Animal Ecology subjects. This research method is Quasi Experimental Design with Non Equivalent Control Group Pretest-Posttest Design in Experimental groups through combined Problem Based Learning. Blended Learning. The sample of this research is Biology Education students of FKIP Universitas Samudra. The research instrument used cognitive tests in the form of Essay questions and ARCS motivation questionnaires. Qualitative data analysis by testing Validity and Reliability. Hypothesis testing with the prerequisite test for data normality and paired t sample t test. The results of the study obtained the value of t arithmetic = 13.61 or with Sig (2-tailed) (0.00) α α (0.05) thus Ha was accepted that the significant cognitive learning outcomes of students occurred through learning Blended Learning-based Problem Based Learning. Student learning motivation is categorized into three: very high, high, and medium. The percentage of students in the three categories is 30%, 63.33%, and 7% respectively.